2012
DOI: 10.3141/2308-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Reported Speeds from Corresponding Fixed-Point and Probe-Based Detection Systems

Abstract: Point-based traffic sensors, such as microwave radar and acoustic sensors, provide the valuable capability of sampling the entire traffic stream. However, full network coverage with point sensors requires a significant initial capital investment and ongoing maintenance expenditures. Probe-based sensors can cover an extensive roadway network at a much lower cost because roadway-based field equipment is not required. Decisions regarding the relative level of point sensor- versus probe-based deployment for traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…However, Hu et al [28] reported that the magnitude of correlation varied with GT speeds for the arterials, ranging from −0.236 to 0.360, and the highest correlation was observed when the speed was between 40 and 45 mph. Chase et al [29] reported that the speed differences were normally distributed with a mean speed difference greater than 5 mph, and the nonsystematic differences were found to be caused by the time lag in recovery from slow speeds, which had an impact on the speed-flow relationship. Kim et al [30] evaluated INRIX speeds over a two-month period, including recurrent and nonrecurrent events.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Hu et al [28] reported that the magnitude of correlation varied with GT speeds for the arterials, ranging from −0.236 to 0.360, and the highest correlation was observed when the speed was between 40 and 45 mph. Chase et al [29] reported that the speed differences were normally distributed with a mean speed difference greater than 5 mph, and the nonsystematic differences were found to be caused by the time lag in recovery from slow speeds, which had an impact on the speed-flow relationship. Kim et al [30] evaluated INRIX speeds over a two-month period, including recurrent and nonrecurrent events.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al (3) observed a clear latency for reporting GPS-based data as well. Chase et al (4) further stated that GPS-probe data has greater latency when travel speed recovers after peak period, than the beginning of a peak period. None of these papers proposed a detailed quantitative latency measurement methodology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Microwave radar detection is highly accurate even in the foggy or rainy weather, [5,6] but it does not support multidirectional distance CONTACT Jing Chen cj@hdu.edu.cn measurement and the sensors are expensive. [7] Laser radar is accurate and cheap, [8] but prone to be affected by light rays. [9] The sensor performance will be degraded in the rains.…”
Section: Introductionmentioning
confidence: 99%